4‐O‐methylhonokiol, a PPARγ agonist, inhibits prostate tumour growth: p21‐mediated suppression of NF‐κB activity. (20th February 2013) - Lee, NJ; Oh, JH; Ban, JO; Shim, JH; Lee, HP; Jung, JK; Ahn, BW; Yoon, DY; Han, SB; Ham, YW; Hong, JT
<x xml:space="preserve">Abstract</x> Background and Purpose The effects of 4‐O‐methylhonokiol (MH), a constituent of Magnolia officinalis, were investigated on human prostate cancer cells and its mechanism of action elucidated. Experimental Approach The anti‐cancer effects of MH were examined in prostate cancer and normal cells. The effects were validated in vivo using a mouse xenograft model. Key Results MH increased the expression of PPARγ in prostate PC‐3 and LNCap cells. The pull‐down assay and molecular docking study indicated that MH directly binds to PPARγ. MH also increased transcriptional activity of PPARγ but decreased NF‐κB activity. MH inhibited the growth of human prostate cancer cells, an effect attenuated by the PPARγ antagonist GW9662. MH induced apoptotic cell death and this was related to G0‐G1 phase cell cycle arrest. MH increased the expression of the cell cycle regulator p21, and apoptotic proteins, whereas it decreased phosphorylation of Rb and anti‐apoptotic proteins. Transfection of PC3 cells with p21 siRNA or a p21 mutant plasmid on the cyclin D1/ cycline‐dependent kinase 4 binding site abolished the effects of MH on cell growth, cell viability and related protein expression. In the animal studies, MH inhibited tumour growth, NF‐κB activity and expression of anti‐apoptotic proteins, whereas it increased the transcriptional activity and expression of PPARγ, and the expression of apoptotic proteins and p21 in tumour tissues. Conclusions and Implication MH inhibits growth of human prostate cancer cells through activation of PPARγ, suppression of NF‐κB and arrest of the cell cycle. Thus, MH might be a useful tool for treatment of prostate cancer.